2021
DOI: 10.1155/2021/6598726
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virtual Reality Training Strategy for Poststroke Patients: A Randomized Clinical Trial

Abstract: Stroke patients suffer impairments including sensory, motor, visual, and cognitive areas, as well as gait and balance manifestations making activities of daily living difficult. In such conditions, virtual reality training can be a potential rehabilitation tool in comparison to conventional physical therapy to cater to the burden of this disability; hence, this randomized clinical trial compared the effects of virtual reality training and conventional physical therapy on balance and lower extremity function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
5
0
6
Order By: Relevance
“…A total of 4153 relevant studies were obtained in the preliminary search, including 385 from CNKI, 770 from Wanfang, 493 from PubMed, 1081 from EMBASE, and 1424 from the Cochrane Library. After exclusion of duplicate studies and strictly adherence to the inclusion and exclusion criteria, 74 randomized controlled trials 8–81 were included. Except for a three-arm experiment, 52 all double-arm experiments with a total of 5128 patients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4153 relevant studies were obtained in the preliminary search, including 385 from CNKI, 770 from Wanfang, 493 from PubMed, 1081 from EMBASE, and 1424 from the Cochrane Library. After exclusion of duplicate studies and strictly adherence to the inclusion and exclusion criteria, 74 randomized controlled trials 8–81 were included. Except for a three-arm experiment, 52 all double-arm experiments with a total of 5128 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Written informed consent was obtained from each participant prior to data collection. The participants were randomly assigned to two groups by lottery method: VR (n=37) and routine physical therapy (n=37) groups [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stroke is seen to be more prevalent in countries like Pakistan, as the people are more inclined toward using local drugs like naswar, pipe smoking, and beetle leaf chewing (paan). Thus, there is higher incidence of stroke in middle-aged populations (<45 years) [ 14 - 16 ]. The study aimed for a younger population with stroke and found cost-effective treatment protocols at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Se obtuvieron 17 artículos para incluir en la revisión bibliográfica. Todos los artículos incluidos en la revisión fueron de tipo ensayo clínico, ensayo controlado aleatorio (Adomavičienė et al, 2019;Anwar et al, 2021;Chen et al, 2022;Cho & Lee, 2019;Choi et al, 2019;Faria et al, 2020;Huang et al, 2022;Long et al, 2020;Maier et al, 2020;Oh et al, 2019;Park et al, 2021;Rodríguez-Hernández et al, 2021Sana et al, 2023;Schuster-Amft et al, 2018;Yang et al, 2022;Yao et al, 2020).…”
Section: Características Del Estudiounclassified
“…En 7 (Anwar et al, 2021;Choi et al, 2019;Faria et al, 2020;Huang et al, 2022;Long et al, 2020;Maier et al, 2020;Yang et al, 2022) estudios las intervenciones fueron a pacientes con ACV crónico, 7 (Chen et al, 2022;Oh et al, 2019;Rodríguez-Hernández et al, 2021Sana et al, 2023;Yao et al, 2020) estudios intervinieron en pacientes con ACV subagudo y en 3 estudios (Adomavičienė et al, 2019;Cho & Lee, 2019;Park et al, 2021;Schuster-Amft et al, 2018) la intervinieron a pacientes con ACV agudo.…”
Section: Características Del Estudiounclassified